The marine geology of False Bay - Bowie, D K (Department of Geological Sciences, 2025)
The marine geology of False Bay, lying in the southwestern extremity of the Southern African continent, has been investigated, The object of the study was to elucidate certain problems associated with marine terracing developed in the area and to describe the nature and distribution of sediments occurring on the floor of the bay with emphasis on the distribution as related to both bottom and surf current patterns. In past literature reference has been made to raised beaches at elavations of 50 to 60 ft; 20 to 25 ft; and 10 to 14 ft. The writer has surveyed certain of these features and has shown that erroneous elevations have been quoted, resulting in inaccurate age designations. Global dating of terraces, exposed and submerged1 is discussed and applied to the features in the Bay, in an attempt to record their history. The oldest feature, the Gordons Bay boulder beach at approximately 100 ft. above mean sea-level, is dated by the writer as of Great Interglacial age. It is pointed out that the Stellenbosch river terraces, dated by A. Krige (1927) as Last Interglacial, can in no way be related to this period. Evidence is presented which suggests that the 50 to 60 ft., 20 to 25 ft. and 10 to 14 ft. terraces formed during the Main, Intra and Late Monastrian periods respectively.